The roles of epigallocatechin gallate in the tumor microenvironment, metabolic reprogramming, and immunotherapy - Li, Dongming; Cao, Donghui; Sun, Yuanlin; Cui, Yingnan; Zhang, Yangyu; Jiang, Jing; Cao, Xueyuan (Frontiers in Immunology, 2024)
Cancer, a disease that modern medicine has not fully understood and conquered, with its high incidence and mortality, deprives countless patients of health and even life. According to global cancer statistics, there were an estimated 19.3 million new cancer cases and nearly 10 million cancer deaths in 2020, with the age-standardized incidence and mortality rates of 201.0 and 100.7 per 100,000, respectively. Although remarkable advancements have been made in therapeutic strategies recently, the overall prognosis of cancer patients remains not optimistic. Consequently, there are still many severe challenges to be faced and difficult problems to be solved in cancer therapy today.Epigallocatechin gallate (EGCG), a natural polyphenol extracted from tea leaves, has received much attention for its antitumor effects. Accumulating investigations have confirmed that EGCG can inhibit tumorigenesis and progression by triggering apoptosis, suppressing proliferation, invasion, and migration, altering tumor epigenetic modification, and overcoming chemotherapy resistance. Nevertheless, its regulatory roles and biomolecular mechanisms in the immune microenvironment, metabolic microenvironment, and immunotherapy remain obscure. In this article, we summarized the most recent updates about the effects of EGCG on tumor microenvironment (TME), metabolic reprogramming, and anti-cancer immunotherapy. The results demonstrated EGCG can promote the anti-cancer immune response of cytotoxic lymphocytes and dendritic cells (DCs), attenuate the immunosuppression of myeloid-derived suppressor cells (MDSCs) and regulatory T cells (Tregs), and inhibit the tumor-promoting functions of tumor-associated macrophages (TAMs), tumorassociated neutrophils (TANs), and various stromal cells including cancer-associated fibroblasts (CAFs), endothelial cells (ECs), stellate cells, and mesenchymal stem/stromal cells (MSCs).Additionally, EGCG can suppress multiple metabolic reprogramming pathways, including glucose uptake, aerobic glycolysis, glutamine metabolism, fatty acid anabolism, and nucleotide synthesis.Finally, EGCG, as an immunomodulator and immune checkpoint blockade, can enhance immunotherapeutic efficacy and may be a promising candidate for antitumor immunotherapy. In conclusion, EGCG plays versatile regulatory roles in TME and metabolic reprogramming, which provides novel insights and combined therapeutic strategies for cancer immunotherapy.